Association between Polymorphism of Interleukin-1beta and Interleukin-1 Receptor Antagonist Gene and Asthma Risk: A Meta-Analysis - Yuanzhou He; Shuang Peng; Weining Xiong; Yongjian Xu; Jin Liu (The Scientific World Journal)
Background. Asthma is a complex polygenic disease in which gene-environment interactions are important. A number of studies have investigated the polymorphism of IL-1β -511C/T and IL-1RA genes in relation to asthma susceptibility in different populations. However, the results of individual studies have been inconsistent. Accordingly, we conducted a comprehensive meta-analysis to investigate the association between the IL-1β -511C/T and IL-1RA polymorphism and asthma risk. Methods. Data were collected from the following electronic databases: Pub Med, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Database (CBM), ISI Web of Knowledge, and Google Scholar Search databases with the last report up to July 2013. Finally, 15 studies were included in our meta-analysis. We summarized the data on the association between IL-1β -511C/T and IL-1RA polymorphism and risk of asthma in the overall population and performed subgroup analyses by ethnicity, mean of age, and source of controls. Odds ratio (OR) and 95% confidence interval (CI) were used to evaluate the associations between IL-1β -511C/T and IL-1RA polymorphism and asthma risk. Statistical analysis was performed with Review Manager 5.1. Results. A total of 15 case-control studies were included in the meta-analysis of IL-1β -511C/T (1,385 cases and 1,964 controls) and IL-1RA (2,800 cases and 6,359 controls) genotypes. No association was found between IL-1β -511C/T polymorphism and asthma risk (dominant model: OR=1.11, 95% CI: 0.99–1.25, P=0.07, PHeterogeneity=0.06; recessive model: OR=1.04, 95% CI: 0.91–1.20, P=0.55, PHeterogeneity=0.11). Subgroup analysis based on ethnicity (Asian and Caucasian), source of controls (population-based controls and hospital-based controls), and mean of age (adulthood and childhood) did not present any significant association. The overall results showed that the IL-1RA polymorphism was related to an increased risk of asthma (homozygote model: OR=1.32, 95% CI: 1.12–1.56, P=0.0009, PHeterogeneity=0.87; recessive model: OR=1.39, 95% CI: 1.18–1.63, P=0.0001, PHeterogeneity=0.82). Similar results were found in the subgroup analyses by ethnicity, mean of age, and source of controls. Sensitivity analysis did not perturb the results. Conclusions. This meta-analysis provided strong evidence that the IL-1RA polymorphism was a risk factor of asthma, especially in Caucasian populations. However, no association was found for IL-1β -511C/T genotype carriers. Larger scale studies are needed for confirmation.